'Data' in the Royal Society's Philosophical Transactions, 1665–1886. (20th September 2020) - Meyns, Chris
Abstract : Was there a concept of data before the so-called 'data revolution'? This paper contributes to the history of the concept of data by investigating uses of the term 'data' in texts of the Royal Society's Philosophical Transactions for the period 1665–1886. It surveys how the notion enters the journal as a technical term in mathematics, and charts how over time it expands into various other scientific fields, including Earth sciences, physics and chemistry. The paper argues that in these texts the notion of data is not used merely as a rhetorical category, and also cannot strictly be identified with the category of evidence. Instead, the notion comes with an associated epistemic structure, one that is in line with its development from an early mathematical use.